The use of the Korean first person possessive pronoun nay vis-à-vis wuli - Lee, Hye Kyung (Language and Linguistics, 2020)
This paper takes a corpus-driven approach to the Korean first person possessive pronoun nay with reference to its plural counterpart wuli. The examination of the frequent noun collocates of the two pronouns in Sejong Corpus reveals the close connection between nay and inalienable entities as well as persons lower than the speaker. Meanwhile, wuli is strongly coupled with places or organizations alongside persons higher than the speaker. Pragmatic principles account for the difference between the kinship term collocates of the two pronouns, such as Horn's (1984; 1989) R-principle or Levinson's (2000) M-principle. The non-prototypical singular use of wuli triggers a pragmatic effect of expressing, for example, affection. The frequent collocation of nay with foreign/loan nouns is a reflection of the tendency that people more interested in social mobility (younger generation and women) are more ready to employ nay rather than the singular wuli and to accept foreign/loan words. The meaning of nay emerging from its interaction with noun collocates is that it is closely connected with being inalienable, private, or unshared. Meanwhile, the singular meaning of wuli is pragmatically derived, which is construed as being grouped, deferent, or general.
Keywords: Corpus-based approach; First person pronouns; Nay; Non-prototypical; Possessives